Intermittent screening using ultra-sensitive malaria rapid diagnostic test and treatment with pyronaridine-artesunate compared to standard preventive treatment with sulfadoxine-pyrimethamine for malaria prevention in pregnant women in Kinshasa, DRC - Japhet Kabalu Tshiongo; Flory Luzolo Khote; Melissa Kabena; Hypolite Muhindo Mavoko; Thierry Kalonji-Mukendi; Landrine Luzolo; Henk D. F. H. Schallig; Kassoum Kayentao; Petra F. Mens; Pascal Lutumba; Halidou Tinto; Vivi Maketa (Malaria Journal)
Abstract Background The declining effectiveness of Intermittent Preventive Treatment in pregnancy with sulfadoxine-pyrimethamine (IPTp-SP) due to the emergence of Plasmodium falciparum resistance highlights the need for alternative malaria prevention strategies in pregnant women. A novel approach was proposed: screening with an ultra-sensitive rapid diagnostic test and treating positive with pyronaridine-artesunate (ISTp-uRDT-PA). This trial compared the impact of both strategies on maternal malaria and anaemia, abortion, intrauterine death, birth weight, preterm delivery. Methods This non-inferiority trial, conducted in Kinshasa, enrolled pregnant women in their second and third trimesters. Participants in the IPTp-SP arm (n = 124) received SP at monthly antenatal visit as per guidelines, while those in the ISTp-uRDT-PA arm (n = 126) were screened monthly with an uRDT and treated with PA if positive. Primary outcomes included asymptomatic parasitaemia (uRDT positive without fever) or symptomatic parasitaemia (uRDT positive with fever or history of fever, and parasite density by microscopy during pregnancy. Results Asymptomatic parasitaemia by uRDT during pregnancy was similar in both arms (20.8% in IPTp-SP vs 21.0% in ISTp-uRDT-PA). At delivery, asymptomatic parasitaemia was 51% higher in ISTp-uRDT-PA arm compared to IPTp-SP (cRR = 1.51 [95% CI 0.76–3.00], p = 0.24). Symptomatic parasitaemia by uRDT at delivery showed no significant difference. Malaria by microscopy at enrolment was detected in 34.4% of women. Malaria by microscopy during pregnancy was 9.6% in IPTp-SP and 10.1%. ISTp-uRDT-PA (p = 0.19), decreasing to 3.2% and 0.9%, respectively, at delivery (p = 0.24). Mean haemoglobin concentration at enrolment was 10.1 g/dl in the IPTp-SP and 9.8 g/dl in the ISTp-uRDT-PA with no significant difference in maternal anaemia at delivery (7%; cRR = 1.07 [95% CI 0.87–1.31], p = 0.52). No significant differences were found for spontaneous abortions and in utero death in both arms. The risk of a premature newborn declined by 14% in ISTp-uRDT-PA compared to the IPTp-SP arm (cRR = 0.86 [95% CI 0.29–2.85], p = 0.79) while low-birth-weight was not significantly higher (cRR = 1.74 [95% CI 0.86–3.53], p = 0.12). Conclusion ISTp-uRDT-PA was non inferior to IPTp-SP and can be considered as a future alternative for IPTp-SP in case this intervention can no longer be used due to high SP resistance. Clinical trials registration: NCT04783051.